Synthesis and physicochemical characterization of derivatized xylan-based pH-sensitive green adsorbent hydrogels for potential sustainable and targeted delivery of drugs - Sundaram Khare; Samit Kumar; Chhavi Sharma; Amit Kumar; Dinesh Kumar Mishra (The Bioscan, 2025)
Derivatives of xylans, namely carboxymethyl xylans (CMX), have garnered scientific interest for their potential application as raw materials in the synthesis of biodegradable pH-sensitive green adsorbent hydrogels. The hydrogels were successfully synthesized, as verified by FTIR spectroscopy. The hydrogel with CMX to AA and a weight-by-weight ratio of 1:5 exhibited a maximum swelling percentage of 1534 ± 15.5% in distilled water, maximum porosity (94.26 ± 4.32%), exceptional mechanical strength, and favorable in vitro degradation patterns (12.39 ± 2.46%), which are useful in identifying optimal hydrogels for sustained and targeted drug delivery. The gel-mass fractions were measured to ascertain the physical properties of the gel. Pore diameters were morphologically examined using a scanning electron microscope. This synthesized hydrogel is expected to serve as a powerful substrate for drug delivery and may possess considerable potential in materials science and therapeutic applications. KEYWORDS: Xyaln; Carboxymethyl xyaln (CMX); FTIR Spectroscopy; Scanning Electron Microscopy (SEM); Mechanical Strength; Porosity